ANALISIS KRITERIA PEMILIHAN PEMASOK DALAM E-PROCUREMENT PADA UMKM DENGAN METODE BWM-SMART (Lembaga Pengembangan Kinerja Dosen, 2022)
The selection of supplier is a strategic decision that must be taken by any business including MSMEs. Various efforts in finding the right supplier, one of which is by utilizing information and communication technology, must be taken to ensure business’ viability. In addition, nowadays the search for the best suppliers is not limited by geographical boundaries, but can also take into account the competitive advantages offered by potential suppliers elsewhere using technological help. This study aims to explain the criteria for digital suppliers in MSMEs with multi-criteria decision-making approaches, the best-worst method (BWM) and the simple multi-attribute rating technique (SMART). The attribute scoring the most according to best-worst method is responsiveness, followed by price, product quality, reputation, service, guarantee and lastly delivery.